Developmental paediatrics in primary care: what should we teach?. Issue 6495 (31st August 1985) - Baird, G; Hall, D M
Abstract : There is little agreement about what constitutes good developmental paediatric practice at the level of primary care. Many of the available screening tests are intrinsically unsatisfactory or badly performed, but screening is only a small part of developmental paediatrics. Every primary care doctor should be familiar with the scientific basis of the subject even if a decision is made not to embark on a formal screening programme.